ANALISIS MATERI BAHASA ARAB DAN RELEVANSINYA DALAM MEMBENTUK KOMPETENSI KEISLAMAN MAHASISWA PAI UNIRA MALANG - Aziza, Ilma Fahmi (JIPI (Jurnal Ilmiah Pendidikan Islam), 2025)
This study aims to analyze the relevance of Arabic language instructional materials in supporting the development of Islamic competence among second-semester students of the Islamic Education Study Program (PAI) at Universitas Islam Raden Rahmat (UNIRA) Malang. Islamic competence in this context includes the students' ability to understand, internalize, and practice Islamic teachings through the comprehension of Arabic texts. A qualitative case study approach was employed, with data collected through interviews, observations, and documentation. The results indicate that although Arabic instruction provides a critical linguistic foundation, the current implementation is primarily structural and has yet to fully integrate Islamic content in a contextualized manner. Both lecturers and students affirm the importance of integrative approaches using Islamic texts, thematic methods, and contextual digital resources to enhance learning effectiveness. The study recommends strengthening Arabic curricula with Islamic content integration and fostering inter-course collaboration to better support the development of students' Islamic competence.